Teachers’ Conceptions of Student Engagement in Learning: The Case of Three Urban Schools - Barkaoui, Khaled; Barrett, Sarah Elizabeth; Samaroo, Julia; Dahya, Negin; Alidina, Shahnaaz; James, Carl (Alberta Journal of Educational Research, 2015)
Although student engagement plays a central role in the education process, defining it is challenging. This study examines teachers’ conceptions of the social and cultural dimensions of student engagement in learning at three low-achieving schools located in a low socioeconomic status (SES) urban area. Sixteen teachers and administrators from the three schools participated in two focus group discussions about their definitions of student engagement, indicators of and factors affecting student engagement, and how to facilitate it. The findings indicate that teachers’ conceptions of student engagement have profound ramifications for the ways that they approach their work. Additionally, the teachers recognize that student engagement is a symptom displayed by individuals, but the roots of engagement lay elsewhere. The teachers also described a wide range of strategies to enhance their students' engagement that focused primarily on the student, the teacher and the classroom through improving student-teacher relationships, incorporating out-of-school issues in the curriculum and the classroom, and having teachers show engagement with educational material. We conclude by outlining several implications for practice and policy and by calling for more research on the origins, development and consequences of teachers’ conceptions of student engagement. Alors que l’engagement des élèves joue un rôle central dans le processus éducatif, en définir le sens représente un défi. Cette étude porte sur les conceptions qu’ont les enseignants des dimensions sociales et culturelles de l’engagement des élèves dans trois écoles peu performantes situées dans des régions urbaines à faible statut socioéconomique. Seize enseignants et administrateurs de trois écoles ont participé à des discussions thématiques de groupe pour partager ce qu’ils entendaient par « engagement des élèves », les indicateurs de celui-ci, les facteurs qui l’influençaient et les moyens de le faciliter. Les résultats indiquent que les conceptions qu’ont les enseignants de l’engagement des élèves ont des répercussions profondes sur leur façon d’aborder leur travail. De plus, les enseignants reconnaissent que l’engagement des élèves est un symptôme que manifeste une personne, mais que les racines en sont ailleurs. Les enseignants ont décrit une vaste gamme de stratégies qui visent l’augmentation de l’engagement des élèves, qui sont axées surtout sur l’élève, l’enseignant et la salle de classe, et qui reposent sur l’amélioration du rapport enseignant-élève, l’intégration d’enjeux externes dans le programme d’études et une manifestation d’engagement de la part des enseignants avec la matière à l’étude. Nous concluons en présentant les grandes lignes des incidences de cette étude sur la pratique et la politique, et en réclamant davantage de recherche sur les origines, le développement et les conséquences des conceptions qu’ont les enseignants de l’engagement des élèves.